Receptor depletion and recovery in small-intestinal neuroendocrine tumors and normal tissues after administration of a single intravenous dose of octreotide measured by 68Ga-DOTATOC PET/CT - Ulrika Jahn (SpringerOpen, 2021)
Abstract Background Low-grade neuroendocrine tumors (NETs) are characterized by an abundance of somatostatin receptors (SSTR) that can be targeted with somatostatin analogs (SSA). When activated with a single dose of SSA, the receptor-ligand complex is internalized, and the receptor is by default recycled within 24 h. Ongoing medication with long-acting SSAs at 68Ga-DOTA-SSA-PET has been shown to increase the tumor-to-normal organ contrast. This study was performed to investigate the time-dependent extended effect (7 h) of a single intravenous dose of 400 µg short-acting octreotide on the tumor versus normal tissue uptake of 68Ga-DOTATOC. Methods Patients with small-intestinal NETs received a single intravenous dose of 400 µg octreotide and underwent dynamic abdominal 68Ga-DOTATOC-PET/CT at three sessions (0, 3 and 6 h) plus static whole-body (WB) PET/CT (1, 4 and 7 h), starting each PET/CT session by administering 167 ± 21 MBq, 23.5 ± 4.2 µg (mean ± SD, n = 12) of 68Ga-DOTATOC. A previously acquired clinical whole-body 68Ga-DOTATOC scan was used as baseline. SUV and net uptake rate Ki were calculated in tumors, and SUV in healthy organs. Results Tumor SUV decreased significantly from baseline to 1 h post-injection but subsequently increased over time and became similar to baseline at 4 h and 7 h. The tumor net uptake rate, Ki, similarly increased significantly over time and showed a linear correlation both with SUV and tumor-to-blood ratio. By contrast, the uptake in liver, spleen and pancreas remained significantly below baseline levels also at 7 h and the receptor turn-over in tumors thus exceeded that in the normal tissue, with restitution of tumor 68Ga-DOTATOC uptake mainly completed at 7 h. These results however differed depending on tumor size, with significant increases in Ki and SUV between the 1st and 2nd PET, in large tumors (≥ 4 mL) but not in small (> 1 to  < 4 mL) tumors. Conclusion SSTR recycling is faster in small-intestinal NETs than in liver, spleen and pancreas. This opens the possibility to protect normal tissues during PRRT by administering a single dose of cold peptide hours before peptide receptor radionuclide therapy (PRRT), and most likely additionally improve the availability and uptake of the therapeutic preparation in the tumors.